2020
DOI: 10.1038/s41467-020-19726-5
|View full text |Cite
|
Sign up to set email alerts
|

In-situ visualization of the space-charge-layer effect on interfacial lithium-ion transport in all-solid-state batteries

Abstract: The space charge layer (SCL) is generally considered one of the origins of the sluggish interfacial lithium-ion transport in all-solid-state lithium-ion batteries (ASSLIBs). However, in-situ visualization of the SCL effect on the interfacial lithium-ion transport in sulfide-based ASSLIBs is still a great challenge. Here, we directly observe the electrode/electrolyte interface lithium-ion accumulation resulting from the SCL by investigating the net-charge-density distribution across the high-voltage LiCoO2/argy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(126 citation statements)
references
References 63 publications
3
122
0
1
Order By: Relevance
“…The total conductivity of the synthesized LPSCl SEs using blocking stainless steel electrodes was 3.2 × 10 −3 S•cm −1 as reported previously. [26] First-Principles Calculations: Based on density functional theory (DFT), the first-principles calculations in this work were performed to investigate the potential decomposition reactions and Li-ion transport dynamics at the interface. The calculations were achieved by Vienna Ab initio Simulation Package (VASP) within the projector augmented-wave (PAW) approach, and the Perdew-Burke-Ernzerhof (PBE) generalized gradient approximation functional was employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total conductivity of the synthesized LPSCl SEs using blocking stainless steel electrodes was 3.2 × 10 −3 S•cm −1 as reported previously. [26] First-Principles Calculations: Based on density functional theory (DFT), the first-principles calculations in this work were performed to investigate the potential decomposition reactions and Li-ion transport dynamics at the interface. The calculations were achieved by Vienna Ab initio Simulation Package (VASP) within the projector augmented-wave (PAW) approach, and the Perdew-Burke-Ernzerhof (PBE) generalized gradient approximation functional was employed.…”
Section: Methodsmentioning
confidence: 99%
“…[25] Therefore, the LZPO-LCO/In-Li all-solid-state cell shows a much lower overpotential than LCO/In-Li all-solid-state cells (Figure S7a, Supporting Information), indicating a smaller interface impedance with the LZPO buffering layer. [26] After 100 cycles, it can be found that the LCO/In-Li all-solid-state cell shows a discharge capacity of 94.1 mAh•g −1 (Figure 3b) and much larger overpotential (Figure S7b, Supporting Information). By contrast, the LZPO-LCO/In-Li all-solid-state cell can still exhibit a high discharge capacity of 136.9 mAh•g −1 , which is nearly 145% of that without the LZPO buffering layer.…”
Section: Effectiveness Of Lzpo Buffering Layermentioning
confidence: 99%
“…[ 118 ] Very recently, Wang et al adopted the in situ differential phase contrast scanning transmission electron microscopy technique to investigate the SCL effect at LCO–Li 6 PS 5 Cl interface. [ 119 ] Undoubtedly, these important techniques will indicate new approaches and insights for studying the SCL at AM–SE interfaces in the future.…”
Section: Interfaces Within High‐voltage Asslbsmentioning
confidence: 99%
“…The BIEF is also applied in lithium-ion batteries. Qiao et al [25] demonstrated a BIEF to reduce the space charge layer formation and boost lithium-ion transport in all-solid-state lithium-ion batteries by an in-situ differential phase contrast scanning transmission electron microscopy technique and finite element method simulations.…”
mentioning
confidence: 99%
“…According to our previous research, the BIEF can be formed by a Schottky heterojunction [24] , intrinsicnegative (i-n) heterojunction [12] and p-n heterojunction [25] . In a Schottky heterojunction, the BIEF can be built up simply at the interface of the metal (electrode) and semiconductor (electrolyte) regions.…”
mentioning
confidence: 99%